Coins of Andraba city -Study in the history of the political city- - Suhail, Mohammed Hassan (Journal of Humanities & Social Sciences, 2019)
In the Islamic era through the inscription of he economic and political history of the city Andiraba of the Code of money multiplied by the city’s historical information codified for the first time did not record it contemporary historical sources, the study showed that the city rotation on its local families governor the authority of the ’Abbasid caliphate under the supervision of the samanid principality that ruled the territory is an important financial center in Andiraba what is behind the river period (261-389e/874-998m),the city of Islamic era, where it mines silver metal silver center Lasik dirhams in the territory of the Islamic East without the money to the princes of the city and the dates of their judgment as well as the names of the rulers of the Islamic Emirates that ruled the Islamic East in the Middle Ages